2015
DOI: 10.1039/c4ra09048a
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hierarchical self-supported NiCo2O4/carbon nanotube core–shell networks as high performance supercapacitor electrodes

Abstract: Three-dimensional (3D) hierarchical self-supported NiCo 2 O 4 /carbon nanotubes/nickel foam (NiCo 2 O 4 /CNT/NF) electrode has been developed by electrodepositing NiCo layered double hydroxides (LDH) on self-supported CNT layer grown on macroporous NF substrate followed by a simple post-annealing process. The resulting 3D hierarchical self-supported NiCo 2 O 4 /CNT/NF electrode delivered high specific capacitances of 1533 F g -1 and 1335 F g -1 at current densities of 3 A g -1 and 30 A g -1 , respectively, vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…Hence these are effectively utilized in variety of applications such as electromechanical actuators, 1 field-effect transistors, 2 sensors, 3 catalyst support materials for proton exchange membrane fuel cells, 4 electrodes for supercapacitors, 5 etc. Hence these are effectively utilized in variety of applications such as electromechanical actuators, 1 field-effect transistors, 2 sensors, 3 catalyst support materials for proton exchange membrane fuel cells, 4 electrodes for supercapacitors, 5 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hence these are effectively utilized in variety of applications such as electromechanical actuators, 1 field-effect transistors, 2 sensors, 3 catalyst support materials for proton exchange membrane fuel cells, 4 electrodes for supercapacitors, 5 etc. Hence these are effectively utilized in variety of applications such as electromechanical actuators, 1 field-effect transistors, 2 sensors, 3 catalyst support materials for proton exchange membrane fuel cells, 4 electrodes for supercapacitors, 5 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various hybrid electrode materials, C-TMO composite has gained particular interest since it combines the advantages of both components while reducing their shortcomings. [36,60,[72][73][74][75] Here, we present recent development on the preparation of C-TMO composite material as an active electrode towards SCs. This section will give insight on the specific role of carbon as well as TMOs, with particular emphasis on the carbon as active support, core element, and conductive substrate.…”
Section: Recent Progress In the Development Of C-tmo Hybrid Electrodementioning
confidence: 99%
“…In particular, the distinct rectangular CV curve at lower potential window was due to the electric double layer formed between the electrode and hydroxyl ions, and the pair of clear redox peaks displayed at higher potential is an indication of the rapid and reversible redox reactions between metal and hydroxyl ions. [74,81] Attributed to the synergistic effects of CNF and NCO, the hybrid material displays high specific capacitance and energy density of 1188.19 F g À 1 and 37.23 W. h kg À 1 , respectively even at high current density of 50 A g À 1 . Similarly, Nitin et al reported the facile and efficient glycine-assisted hydrothermal route for the cube-like iron oxide nanoparticles supported on ordered multimodal porous carbon (OMPC).…”
Section: Carbon As Active Supportmentioning
confidence: 99%
“…Carbon nanotubes (CNTs), have been introduced to increase the conductivity and cycle life of Ni(OH) 2 due to theirs well-defined nanostructure, high electrical conductivity and chemical stability, [21][22]. Recently, many works of CNTs/NiO or CNTs/Ni(OH) 2 have been reported, such as three-dimensional hierarchical self-supported NiCo 2 O 4 /carbon nanotube core-shell networks [23], ultrathin β Ni(OH) 2 nanoplates vertically grown on nickel-coated carbon nanotubes [24], and carbon nanotube/NiO x (OH) y nanocomposite [25]. But, the degradation in specific capacitance caused by the materials aggregation is also a handicap to provide excellent electrochemical stability and cycle life [26].…”
Section: Introductionmentioning
confidence: 99%